End‐of‐life decision‐making and advance care directives in Italy. A report and moral appraisal of recent legal provisions. (2nd July 2019) - Botti, Caterina; Vaccari, Alessio
Abstract: The present article reviews the state of public debate and legal provisions concerning end‐of‐life decision‐making in Italy and offers an evaluation of the moral and legal issues involved. The article further examines the content of a recent law concerning informed consent and advance treatment directives, the main court pronouncements that formed the basis for the law, and developments in the public debate and important jurisprudential acts subsequent to its approval. The moral and legal grounds for a positive evaluation of this law, which attests that the patient may withhold or withdraw from life‐prolonging treatment, will be offered with reference to liberal approaches and particularly to the frameworks of care and virtue ethics; but reasons will also be offered in order to consider not only the latter but also broader range of end‐of‐life treatment decisions as morally apt options. In this light, we argue in favour of a further development of the Italian legislation to encompass forms of assisted suicide and active euthanasia.